2013
DOI: 10.1093/cid/cit665
|View full text |Cite
|
Sign up to set email alerts
|

Primary Care Guidelines for the Management of Persons Infected With HIV: 2013 Update by the HIV Medicine Association of the Infectious Diseases Society of America

Abstract: Evidence-based guidelines for the management of persons infected with human immunodeficiency virus (HIV) were prepared by an expert panel of the HIV Medicine Association of the Infectious Diseases Society of America. These updated guidelines replace those published in 2009. The guidelines are intended for use by healthcare providers who care for HIV-infected patients. Since 2009, new antiretroviral drugs and classes have become available, and the prognosis of persons with HIV infection continues to improve. Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
355
2
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 395 publications
(368 citation statements)
references
References 85 publications
6
355
2
5
Order By: Relevance
“…In the present study, the reversion rate of QFT-IT was high (81 ) in patients completing IPT, while reversion were not detected in those without IPT. The reversion rate was higher than those reported in either the HIV-infected persons of the Norwegian study (23 ; 15) or the non-HIV-infected cohort (5-42 ) (11,13,14,(18)(19)(20). The higher reversion rate in our study than in the Norwegian study could be because of our higher rate of compliance to LTBI treatment, lower median IFN-γ baseline level (1.05 IU mL vs. 3.48 IU mL), and a higher proportion of patients completing serial QFT-IT testing (95 vs. 52 ) enabling more accurate assessment of IFN-γ responses.…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…In the present study, the reversion rate of QFT-IT was high (81 ) in patients completing IPT, while reversion were not detected in those without IPT. The reversion rate was higher than those reported in either the HIV-infected persons of the Norwegian study (23 ; 15) or the non-HIV-infected cohort (5-42 ) (11,13,14,(18)(19)(20). The higher reversion rate in our study than in the Norwegian study could be because of our higher rate of compliance to LTBI treatment, lower median IFN-γ baseline level (1.05 IU mL vs. 3.48 IU mL), and a higher proportion of patients completing serial QFT-IT testing (95 vs. 52 ) enabling more accurate assessment of IFN-γ responses.…”
Section: Discussioncontrasting
confidence: 63%
“…These findings suggest that frequent serial IGRA tests may be useful for monitoring IPT response, especially in cases where the drug resistance of M. tuberculosis is unknown. Other studies have reported similar responses of IFN-γ after LTBI treatment in both non-HIV-infected (11,13,14,18,19) and HIV-infected individuals (15). However, studies on non-HIV-infected patients have reported that the significant decrease of IFN-γ level occurred regardless of compliance to LTBI treatment (14,20).…”
Section: Discussionmentioning
confidence: 85%
“…53 In the fi eld of HIV/AIDS, viral load determination has become a routine test and is the basis of clinical patient management. 54 Although the commutability of some materials might need additional work to yield consensus, 55 clearly these eff orts have a positive eff ect on comparability between assays. 56 Eff orts towards standardising fi lovirus assays hold the promise of similar eff ects and should be vigorously pursued.…”
Section: Personal Viewmentioning
confidence: 99%
“…For this reason, the Infectious Disease Society of America recommends screening for dyslipidemia prior to initiating ART and three to six months after starting therapy and at least annually thereafter [20].…”
Section: Introductionmentioning
confidence: 99%